Phosphorus Recovery and Recycling - Zhang, Tao (IntechOpen, 2019)
Phosphorus, as a common chemical substance, plays an important role in human life, but also causes serious harm to the environment. The recovery and utilization of phosphorus is extremely urgent. The series of studies carried out by the author are described in detail in this book.